IMPROVING CLEAN AND HEALTHY LIVING BEHAVIOR (PHBS) AMONG SCHOOL CHILDREN THROUGH HEALTH EDUCATION - Puspita, Enny; Aziz, Aditya Nuraminudin (Journal of Indonesian Public Health Service, 2025)
Clean and Healthy Living Behavior (PHBS) is an essential component of health promotion aimed at preventing disease and improving the quality of life, particularly among school-aged children. However, the implementation of PHBS among school children remains suboptimal due to limited knowledge and awareness of healthy practices. This community service activity aimed to improve PHBS among school children through structured health education. The activity was conducted at an elementary school using interactive educational methods, including lectures, visual media, demonstrations, and question-and-answer sessions. The target participants were school-aged children who actively took part in the health education program. The results showed an improvement in students’ knowledge, attitudes, and practices related to PHBS after the intervention. Students demonstrated a better understanding of clean and healthy behaviors, particularly proper handwashing techniques, personal hygiene, and environmental cleanliness. Increased participation and positive responses during the activity indicated that health education effectively enhanced students’ awareness and willingness to apply PHBS in their daily school activities. In conclusion, health education plays a significant role in promoting Clean and Healthy Living Behavior among school children. School-based health education programs are recommended as a sustainable strategy to foster healthy habits from an early age and to support the creation of a healthy school environment.